Integrating three comprehensive data sets shows that mitochondrial DNA variation is linked to species traits and paleogeographic events in European butterflies. (23rd August 2019) - Dapporto, Leonardo; Cini, Alessandro; Vodă, Raluca; Dincă, Vlad; Wiemers, Martin; Menchetti, Mattia; Magini, Giulia; Talavera, Gerard; Shreeve, Tim; Bonelli, Simona; Casacci, Luca Pietro; Balletto, Emilio; et al.
Abstract: Understanding the dynamics of biodiversity, including the spatial distribution of genetic diversity, is critical for predicting responses to environmental changes, as well as for effective conservation measures. This task requires tracking changes in biodiversity at large spatial scales and correlating with species functional traits. We provide three comprehensive resources to understand the determinants for mitochondrial DNA differentiation represented by (a) 15, 609 COI sequences and (b) 14 traits belonging to 307 butterfly species occurring in Western‐Central Europe and (c) the first multi‐locus phylogenetic tree of all European butterfly species. By applying phylogenetic regressions we show that mitochondrial DNA spatial differentiation (as measured with G ST, G ′ST, D and D ST ) is negatively correlated with species traits determining dispersal capability and colonization ability. Thanks to the high spatial resolution of the COI data, we also provide the first zoogeographic regionalization maps based on intraspecific genetic variation. The overall pattern obtained by averaging the spatial differentiation of all Western‐Central European butterflies shows that the paradigm of long‐term glacial isolation followed by rapid pulses of post‐glacial expansion has been a pervasive phenomenon in European butterflies. The results and the extensive data sets we provide here constitute the basis for genetically‐informed conservation plans for a charismatic group in a continent where flying insects are under alarming decline.